Comparação da utilização de biomassa in natura na geração de energia em uma termelétrica de 66 MW - Zinza Junior, Emanoel (Universidade Estadual Paulista (Unesp), 2022)
The global energy matrix is being remodeled, with an increasing share of renewable sources, with biomass being considered the third largest source of energy in the world. The work aims to manufacture 100% jaraguá gr grass/charcoal b ass briquettes and the lend and analyze the in natura residues for the production of electricity in a 66 MW thermoelectric power plant. A mixture of 75% jaraguá grass and 25% charcoal fines was made, obtaining a higher calorific value of 21 023J/g. With a hydraulic press, the sam ples were briquetted at a pressure of 15,000 kg/cm3 for one minute. Through the immediate chemical analysis performed in triplicate, it was observed that the blend had 10.3% of ash content and 42.7% of volatile conten t , resulting in 47% fixed carbon. In th e durability test, a durability of 13% was obtained for the blend and for the jaraguá grass briquette of 93% durability. From the definition of a mathematical model of a thermoelectric power plant and a comparative an alysis between in natura biomass as fue ls, it was proved that the use of blends for thermoelectric generation is viable, as the amount of biomass used is reduced, in addition to supplying the negative effects of seasonality during the year with the use of residues with similar elementary charac teristics.

A matriz energética mundial está se remodelando, passando a ter uma participação cada vez maior das fontes renováveis, sendo a biomassa considerada a terceira maior fonte de energia do mundo. O trabalho tem por objetivo a confecção dos briquetes 100% de capim jaraguá e da blenda capim/carvão e analisar os resíduos in natura para a produção de energia elétrica em uma usina termelétrica de 66 MW. Uma mistura de 75% capim jaraguá e 25% de finos de carvão foi feita obtendo-se um poder calorifico superior de 21023J/g. Com uma prensa hidráulica efetuou-se a briquetagem das amostras a uma pressão de 15.000 kg/cm3durante um minuto. Por meio da análise química imediata realizada em triplicata, observou-se que a blenda apresentou 10,3% de teor de cinzas e 42,7% de teor de voláteis, resultando em 47% de carbono fixo. No teste de durabilidade obteve-se uma durabilidade de 13% para a blenda e para o briquete de capim jaraguá de 93% de durabilidade. A partir da definição de um modelo matemático de uma usina termoelétrica e análise comparativa entre as biomassas in natura como combustíveis comprovou-se que é viável a utilização de blendas para a geração termelétrica, pois se reduz a quantidade de biomassa utilizada, além de suprir os efeitos negativos da sazonalidade durante o ano com a utilização de resíduos de características elementares semelhantes.
Comparison of the use of biomass in natura in energy generation in a 66 MW thermelectric
Keywords: Densification; Briquette; Bioenergia; Densificação; Biochar; Briquete